Development and validation of a tool for patient reporting of symptoms and signs of the post-thrombotic syndrome - Utne, Kristin Kornelia; Ghanima, Waleed; Foyn, Siv; Kahn, Susan; Sandset, Per Morten; Wik, Hilde Skuterud (Thrombosis and Haemostasis, 2016)
Post-thrombotic syndrome (PTS) is a long-term complication of deepvein thrombosis (DVT). The Villalta scale is the recommended tool for diagnosing PTS, but requires a clinician’s assessment in addition to patient self-assessment. In the present study, we validated a self-administered tool for patient reporting of leg symptoms and signs as a mean to assess PTS. We first validated a form for patient self-reported Villalta (PRV1), then developed and validated a visually assisted form (PRV2). The validity of PRV1 and PRV2 was assessed in patients diagnosed with DVT between 2004 and 2012. Median time from DVT to inclusion was 5.1 and 3.5 years for PRV1 (n=162) and PRV2 (n=94), respectively. Patients were requested to complete the PRV form before a scheduled visit. PTS diagnosed by the original Villalta scale during the visit served as the reference method. PRV1 showed only moderate agreement for diagnosing PTS compared with the original Villalta scale (kappa agreement 0.60, 95 % CI 0.48–0.72), whereas PRV2 showed very good agreement (0.82, 95 % CI 0.71–0.94). In the validation of PRV2, PTS was diagnosed in 54 (57 %) patients according to the original Villalta scale and in 60 (64 %) by PRV2. The sensitivity of PRV2 to detect PTS was 98 % and the specificity was 83 %. We conclude that the visually assisted form for PRV is a valid and sensitive tool for diagnosing PTS. Such a tool could be applied in further clinical studies of PTS, making studies less resource demanding by reducing the need for in-person clinic visits.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Deep-vein thrombosis; long-term complication; patient-reported outcome; post-thrombotic syndrome; Villalta scale